Safety evaluation of the food enzyme endonuclease from the non‐genetically modified Penicillium citrinum strain NP 11–15 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal, 2024)
Abstract The food enzyme endonuclease (Aspergillus nuclease S1; EC 3.1.30.1) is produced with the non‐genetically modified Penicillium citrinum strain NP 11–15 by Shin Nihon Chemical Co., Ltd. The food enzyme is free from viable cells of the production organism. It is intended to be used in the processing of yeast and yeast products. Dietary exposure to the food enzyme–total organic solids (TOS) was estimated to be up to 0.006 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1010 mg TOS/kg bw per day, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 168,333. A search for homology of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions by dietary exposure cannot be excluded, especially for individuals allergic to Penicillium. However, the likelihood of such reactions will not exceed the likelihood of allergic reactions to Penicillium. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.